The Distributional Effects of International Fragmentation - Wilhelm Kohler (Johannes Kepler University of Linz, Department of Economics, 2002)
Economic globalization causes an increasing international fragmentation (disintegration) of value-added-chains, whereby firms outsource components of production to foreign markets. There is a high level of concern about unwelcome distributional effects. This paper provides a theoretical treatment of this issue within a general Heckscher-Ohlin framework, allowing for an arbitrary number of goods, factors, and fragments. It shows how a fragmented production equilibrium is disturbed by lower costs of fragmentation, and it introduces the concept of effective prices of fragments to derive general results that characterize the distributional consequences of an increase in international fragmentation occurring simultaneously in several industries.
Keywords: D33; F11; F15; F23; 330; Globalisierung; Outsourcing; Faktorproportionentheorem; Welt; Verteilungswirkung